2014
DOI: 10.1002/ejoc.201402067
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Synthesis of Highly Functionalized Furans Through the RuII‐Catalyzed [3+2] Cycloaddition of Diazodicarbonyl Compounds

Abstract: A novel method for the RuII‐catalyzed regioselective synthesis of highly functionalized furans from readily available cyclic and acyclic diazodicarbonyl compounds and terminal alkynes is described. The devised protocol offers a straightforward means to the construction of a variety of diverse furan derivatives through powerful cascade processes, including the formation of ruthenium carbenoid, cyclopropenation, ring‐opening metathesis, and cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 159 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…Lee et al reported the use of ruthenium for the reaction of terminal aryl alkynes and symmetrically substituted cyclic diazodicarbonyl compounds to afford fused bicyclic furan derivatives (Scheme 31, b). 49 Coleman, et al tackled the reaction with the less reactive internal alkynes. 44 Using CuI as the catalyst in neat conditions, tetrasubstitued furans were obtained in moderate yields (Scheme 32, a).…”
Section: Scheme 31mentioning
confidence: 99%
“…Lee et al reported the use of ruthenium for the reaction of terminal aryl alkynes and symmetrically substituted cyclic diazodicarbonyl compounds to afford fused bicyclic furan derivatives (Scheme 31, b). 49 Coleman, et al tackled the reaction with the less reactive internal alkynes. 44 Using CuI as the catalyst in neat conditions, tetrasubstitued furans were obtained in moderate yields (Scheme 32, a).…”
Section: Scheme 31mentioning
confidence: 99%
“…The yield of this ketone when using Ru (PPh 3 ) 3 Cl 2 as a catalyst was 77%. [144] A Rh-catalyzed reaction with oct-1-yne was not selective, and a mixture of 2-and 3-hexyl-4H-indeno[1,2-b]furan-4ones was obtained with a combined yield of 43%. [145] An alternative and simpler non-catalytic route to such ketones was proposed by Reisch (Scheme 29C).…”
Section: H-indeno[12-b]furanmentioning
confidence: 99%
“…In particular, there are no reports of a biological study of naphtho [1,2-b]furan-3-carboxamides. Accordingly, as part of an our ongoing study of the synthesis of bio-active heterocycles [20,[37][38][39][40][41][42][43] and the search for novel anti-tyrosinase, antioxidant, and antibacterial agents [20,21,[44][45][46], diverse naphtho[1,2-b]furan-3-carboxamide derivatives were synthesized starting from 1,4-dihydroxy-2-naphthoic acid via methylation, oxidation, followed by Re 2 O 7 -catalyzed cascade formal [3+2] cycloaddition processes. The synthesized naphtho [1,2-b]furan-3-carboxamides were then evaluated for their anti-tyrosinase, antioxidant, and antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%